OXIDATIVE STRESS BIOMARKERS IN MUSSELS SAMPLED FROM FOUR SITES ALONG THE MOROCCAN ATLANTIC COAST (BIG CASABLANCA) - LAILA EL JOURMI; ABDESSAMAD AMINE; NADIA BOUTALEB; HANANE LABBARDI; SAID LAZAR; SAID EL ANTRI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Catalase (CAT) activity and malondialdehyde (MDA) level in whole bodies of the mussel perna perna, collected from four stations along the Moroccan Atlantic coast (Big Casablanca area), were monitored to evaluate stress effects on mussels collected from the selected sites. The oxidative stress biomarkers showed statistically significant differences at the polluted sites when compared to the control ones. In general, our data indicated that CAT activity and MDA concentration are a higher and significant (p < 0.05) in mussels collected at polluted site when compared to specimen sampled from control ones. In conclusion, the oxidative stress biomarkers response obtained for October 2010 and 2011, clearly demonstrate the potential presence of different contaminants in Site 4 and Site 3 reflecting the intensity of pollution in these areas.